(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: To determine the epidemiological, clinical, paraclinical, and treatment characteristics of children with cyanotic congenital heart disease (CCHD) at Children’s Hospital 2 during 2024. Method: Descriptive case series. Results: A total of 192 children with CCHD were included. Male patients accounted for 54.2%. The mean age was 28.4 ± 37.4 months; the <6-month group represented 27.1%. Children from provinces accounted for 59.4%. Malnutrition was present in 87% of cases. Most patients (88.5%) were diagnosed with CCHD, and 45.8% were hospitalized via referral. Clinically, 12% were admitted in emergencies, 8.3% had concomitant diseases, and 6.3% were diagnosed prenatally. The most common clinical diagnosis was tetralogy of Fallot (58.3%). The mean heart rate was 128 ± 20.4/min, with tachycardia in 29.7%; mean respiratory rate was 34 ± 8.6/min, with tachypnea in 33.9%; 39.1% had chest retractions, 4.7% had loud P2, and 25.5% had hemoconcentration. The most frequent CCHD type was tetralogy of Fallot (46%), followed by pulmonary atresia with VSD (12.5%) and pulmonary atresia with intact ventricular septum (4.2%); truncus arteriosus was the least common (0.5%). Regarding treatment, all cases required medical management. Temporary interventions were performed in 37.8%, and complete repairs in 62.2%. Among tetralogy of Fallot cases, 22.3% underwent temporary intervention and 56.4% completed repair. Temporary cardiac catheterization was performed in 43.6%, including PDA stenting (52.9%), balloon atrial septostomy (35.3%), and RVOT stenting (11.8%). Temporary surgical interventions were performed in 56.4%, including pulmonary artery banding (54.5%), Glenn shunt (36.4%), and Blalock–Taussig shunt (9.1%). Outcomes showed that 94.3% improved after treatment, with a mortality rate of 3.1%. The mean hospital stay was 15.2 ± 16.1 days. Conclusion: The most common CCHD was TOF (46%), followed by PA-VSD (12.5%) and PA-IVS (4.2%); the least common was truncus arteriosus (0.5%). Temporary interventions accounted for 37.8% of cases, while complete repairs accounted for 62.2%. The improvement rate after intervention was 94.3%, with a mortality rate of 3.1% and an average hospital stay of 15.2 ± 16.1 days. These outcomes were more favorable compared with previous periods. However, the prenatal diagnosis rate of CCHD remained low, highlighting the need to strengthen prenatal screening. Pediatric cardiologists should be proficient in the diagnosis and management of CCHD, aiming to reduce temporary interventions and increase complete repairs.